Bonhoeffer on Providence in History - Ballard, P. H. (Scottish journal of theology, 1974)
Bonhoeffer gave surprisingly little systematic attention to questions of providence and history despite the fact that his lifelong theological concern was to explore the way in which revelation was given form in his world. It was only in the experiences in the Second World War when working in the Abwehr with members of the resistance and subsequently in prison, when he had to face the possibility of a major shift in human consciousness, that he looked at the problem of history and the development of culture and had to relate it to an understanding of providence. Even so circumstances did not allow him to work this out in detail; both the Ethics and Letters and Papers from Prison are evidence of a direction in his thinking, though the way seems to be fairly clearly delineated.